An exploratory study on the critical success factors in the implementation of enterprise resource planning systems in Venezuela (Journal of Information Systems and Technology Management, 2005)
This paper reports on an exploratory study, carried out in seven Venezuelan organizations who have successfully implemented an enterprise resource planning (ERP) system. The data were collected by means of both a questionnaire and of conducted interviews to the seven project managers of the project of implementation of ERP systems in these enterprises. The purpose of the study was to know the perceptions the project managers, on aspects and activities of the process of implementing an ERP system and that are strongly correlated with the Critical Success Factors (FCE's) for this kind of projects. The FCE's were identified in a deep revision of the literature. The questionnaire included, among others, questions on the top management support to the project, the process of selection of the system, team work implementation and the participation and training of the users. Additionally were identified the problems that organizations confronted during the implementation process. The study concludes that organizations must take care the elements that indicate the FCE's, because them hit positively the project, additionally describe aspects, which must take into account the enterprises who are in the process to adopt an ERP system to facilitate its implementation.